Design of wideband reflectometer for a microwave imaging system - Seman, NorHudah; Bialkowski, M. E. (2007)
The design of a wideband reflectometer for the purpose of inclusion in a microwave imaging system is described. In order to accomplish reflection coefficient measurements over a large frequency band, wideband couplers, dividers and square-law power detectors are assumed to form the reflectometer. The imperfect operation of the chosen configuration of reflectometer is corrected by using a one-port calibration procedure. The operation of non-calibrated and calibrated instruments is studied with the use of Agilent ADS.